Suffering in Motion: Mobility Strategies of Mexicans Deported from the United States - Radziwinowiczówna, Agnieszka (2019)
Since the beginning of this century we have witnessed the development  of studies critically analyzing deportation and deportability. However,  little is known about the post-deportation trajectories of deportees. This can  be better understood by employing a comprehensive typology of post-deportation strategies of mobility. This article analyzes the case of Mexicans  deported from the United States and draws on ethnography among former  deportees in Oaxaca. Post-deportation mobility anticipates or stems from the absences and suffering experienced by the deported people. It is a form  of mobility that is often an example of agency and resistance, especially in the context of unauthorized return to the United States.